PERHITUNGAN DEBIT BANJIR SUNGAI CIPINANG DAN SUNGAI SUNTER PADA BERBAGAI PERIODE ULANG - Ema Khoirunisa Ovilia; Eri Primadianti; Denny Yatmadi (Construction and Material Journal, 2020)
In the area around the Cipinang and Sunter Rivers, floods often occured due to runoff from overflowing rivers. The data and information used in this study are secondary data from related agencies, namely the Balai Besar Wilayah Sungai Ciliwung-Cisadane and BMKG. Hydrological and hydraulic analysis from existing data yield calculation results the maximum flood discharge for the Sunter River for a 2-year return period is 114.035 m³ / s and for a 100-year return period of 407.589 m3 / s and for the Cipinang River, the discharge for the 2-year return period is 113.214 m3 / s while for the 100 yearly repetition of 405,083 m3 / sec. Keywords : Cipinang River, Sunter River, Flood Flow.